Technological Revolution and Global-Local Transformations: The View from Russia - Yanitsky, Oleg (Advances in Social Sciences Research Journal, 2016)
Under the influence of current Scientific and technological revolution our planet is rapidly transforming into the sociobiotechnical system (the SBT-system) within which social, biological and technological processes are integrated and mutually transformed by open and overt metabolic processes. The SBT-systems existence makes dichotomy approaches like ‘man-nature’, ‘we-they’, etc. obsolescent. The analysis of complexities is needed. The text is the result of the author’s fifty-year studies in globalization and risk theory, social ecology, social movements, urbanization, local elite communities, and primary eco-structures and in other complex systems and processes. The main outcome of the study is that consolidated efforts of all kind of sciences and civic activity are now urgently needed. Another conclusion of the above research is a necessity of permanent being of an actor in the midst of events and discussions on global issues. The base of such consolidated efforts is the problem-oriented and interdisciplinary research which in turn requires new organizational forms and experiences researchers. The SBT-systems analysis may be realized only by problem-oriented interdisciplinary studies of the conflict and struggle between two generalized trends: globalization-universalization and localization aimed at protection of ‘islands’ of natural ecosystems and global SBT-system diversity.